(untitled) (Bangladesh Journal of Botany, 2025)
Salvia species contain very rich bioactive substances. In this study, the essential oil compositions of Salvia dichroantha Stapf (endemic) and S. tomentosa Mill. species collected from their natural area, and their essential oil composition and elemental substance (14 elements) contents were determined. The main components in the essential oils of S. dichroantha and S. tomentosa species were phytol (33.27%) and caryophyllene oxide (23.44%), respectively. It was recorded that the species had higher K and Ca contents from macronutrients and that their heavy metal contents were below the permitted limit values. Bangladesh J. Bot. 54(3): 547-553, 2025 (September)